1988
DOI: 10.1093/nar/16.1.291
|View full text |Cite
|
Sign up to set email alerts
|

The complete nucleotide sequence of the potexvirus white clover mosaic virus

Abstract: The complete nucleotide sequence (5845 nucleotides) of the genomic RNA of the potexvirus white clover mosaic virus (WC1MV) has been determined from a set of overlapping cDNA clones. Forty of the most 5'-terminal nucleotides of WC1MV showed homology to the 5' sequences of other potexviruses. The genome contained five open reading frames which coded for proteins of Mr 147, 417, Mr 26,356, Mr 12,989, Mr 7,219 and Mr 20,684 (the coat protein). The Mr 147,417 protein had domains of amino acid sequence homology with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 27 publications
2
66
0
Order By: Relevance
“…Analogous ORFs are not found in all potexviruses but are present in PMV (Sit et al, 1989) and CYMV (Sit et al, 1990) in which ORF6 encodes a 14K protein. WC1MV RNA of strain M, but not of strain O, encodes a 10K product within ORF1 (Forster et al, 1988) corresponding in size and position to ORF7 found in FMV RNA. The significance of these internal ORFs remains to be established.…”
Section: Nucleotide Sequence and Genome Organizationmentioning
confidence: 95%
See 1 more Smart Citation
“…Analogous ORFs are not found in all potexviruses but are present in PMV (Sit et al, 1989) and CYMV (Sit et al, 1990) in which ORF6 encodes a 14K protein. WC1MV RNA of strain M, but not of strain O, encodes a 10K product within ORF1 (Forster et al, 1988) corresponding in size and position to ORF7 found in FMV RNA. The significance of these internal ORFs remains to be established.…”
Section: Nucleotide Sequence and Genome Organizationmentioning
confidence: 95%
“…The remainder of ORF2 sequences from all other potexviruses are less related to each other than are ORF1 and ORF3 (IlK protein) sequences (Table 3; see also Zuidema et al, 1989). FMV ORF 3 and ORF 4 are related to those of other potexviruses in that they contain stretches of hydrophobic residues predicted to form transmembrane helices (Morozov et al, 1987;Forster et al, 1988;Skryabin et aL, 1988b) bordered by charged residues. Although FMV has the smallest ORF4 of all potexviruses, the common N-terminal hydrophobic region is conserved.…”
Section: Similarity Of the Putative Proteins Of The Fmv Genome To Cormentioning
confidence: 99%
“…It should be noted that the minus strands of two potexvirus RNAs, those of white clover mosaic virus (Forster et al, 1988) and papaya mosaic virus (Sit et al, 1989), also contain ORFs similar in size and location to those in the above-mentioned carlaviruses.…”
Section: Sequence Analysis Of the Putative Protein Encoded By The Cvbmentioning
confidence: 99%
“…Morozov et al (1987) noted that several non-virion proteins of positive-sense RNA-containing plant viruses (potyviruses and carmoviruses) contain highly hydrophobic segments and might be membrane-bound. Small non-virion proteins of potexviruses, hordeiviruses and furoviruses are also hydrophobic and could interact directly with membranes (Morozov et al, , 1989Forster et al, 1988). The hydrophobicity of the PVM proteins was analysed by the method described by Eisenberg et al (1984).…”
Section: Sequencing Of the Cdna Clonesmentioning
confidence: 99%